PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Andriani, Ninik; Nursiam, Nursiam (Riset Akuntansi dan Keuangan Indonesia, 2018)
This study aimed to examine the effect of audit fee, audit tenure, audit rotation and auditor reputation on the audit quality in manufacturing companies listed in Indonesian Stock Exchange of  2013-2015. Population of the research is 117 manufacturing companies listed in Indonesian Stock Exchange of 2013-2015. Sample was taken by using purposive sampling, namely sampling with certain  consideration. Based on the criteria, data sample of 37 manufacturing companies for period of three years were obtained, so that sample was 104 data. The data was analyzed by using descriptive statistic analysis and logistic regression analysis. The result shows that audit tenure, audit rotation and auditor reputation have no influences to the audit quality, and audit fee has significant effect on audit quality. Keywords: audit fee, audit tenure, audit rotation, auditor reputation, audit quality